Perlindungan Hukum Terhadap Korban Kekerasan Seksual Berbasis Elektronik - Dachi, Kornelius Yohan (Universitas Batanghari Jambi, 2024)
Indonesia is a country based on Pancasila. Every citizen is obliged to obey all the rules set by the state. In reality, human rights violations continue to be carried out by irresponsible individuals, one example of which is sexual violence, both physical and non-physical. With the development of technology in the era of globalization, there are now many cases of electronic sexual violence which are classified as non-physical sexual violence. This electronic sexual violence can take the form of distributing intimate content in the form of photos, videos and other electronic documents that contain sexual elements against the wishes of the recipient. Social networks made possible by the Internet function as a means of dissemination. This is the current emergency situation of sexual violence which is very detrimental to both victims and the entire community. The aim of this research is to find out how Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) can provide justice to perpetrators and victims by examining how the law is applied to perpetrators and what legal protection the victims are entitled to. Because this way we will know how legal protection is for victims. This article of the law can function as intended, and the deterrent effect of this law will help minimize the recurrence of electronic sexual violence.